2013
DOI: 10.1097/mbc.0b013e32835e4275
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet activity of L-sulforaphane by regulation of platelet activation factors, glycoprotein IIb/IIIa and thromboxane A2

Abstract: L-sulforaphane was identified as an anticarcinogen that could produce quinine reductase and a phase II detoxification enzyme. In recent decades, multi-effects of L-sulforaphane may have been investigated, but, to the authors' knowledge, the antiplatelet activation of L-sulforaphane has not been studied yet.In this study, 2 μg/ml of collagen, 50 μg/ml of ADP and 5 μg/ml of thrombin were used for platelet aggregations with or without L-sulforaphane. L-sulforaphane inhibited the platelet aggregation dose-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Very little scientific evidence exists for the anti-platelet effects of kale or the expected human metabolites of kale. However, our observations are in keeping with those of Oh et al 35 who reported a significant reduction in collagen-induced GPIIb-IIIa expression after treating platelets with L-sulforaphane, a degradation product of the glucosinolate glucoraphanin. Similarly, glucosinolate-containing alfaalfa (a perennial herb) at 1 mg mL −1 concentration has been shown to inhibit ADP and collagen-induced platelet aggregation by 73 ± 12% and 50 ± 9%, respectively, when assessed by light transmission aggregometry (LTA).…”
Section: Discussionsupporting
confidence: 93%
“…Very little scientific evidence exists for the anti-platelet effects of kale or the expected human metabolites of kale. However, our observations are in keeping with those of Oh et al 35 who reported a significant reduction in collagen-induced GPIIb-IIIa expression after treating platelets with L-sulforaphane, a degradation product of the glucosinolate glucoraphanin. Similarly, glucosinolate-containing alfaalfa (a perennial herb) at 1 mg mL −1 concentration has been shown to inhibit ADP and collagen-induced platelet aggregation by 73 ± 12% and 50 ± 9%, respectively, when assessed by light transmission aggregometry (LTA).…”
Section: Discussionsupporting
confidence: 93%
“…A comparison of platelet activators revealed that collagen was most inhibited by SFN, which markedly decreased collagen-induced glycoprotein IIb/IIIa activation and thromboxane A2 formation in vitro . SFN also reduced collagen and epinephrine-induced pulmonary embolism but did not affect prothrombin time in vivo ; this indicated that SFN might be a potential antithrombotic drug [ 72 , 73 ].…”
Section: Sfn-mediated Protection From Atherosclerosismentioning
confidence: 99%
“…As discussed previously that Radish pods have high amount of alkaloids and isothiocyanate compound, especially sulforaphene and sulforaphane which possess anti-platelet activity that has been reported in several studies (Chuang et al, 2013, Fuentes and Palomo 2014, Jayakumar et al, 2016. However sulforaphane antiplatelet activity is reported in different studies which is due to stimulation of adenylate cyclase, glycoprotein IIb/IIIa as well as thromboxane A2 (Jayakumar et al, 2013, Oh et al, 2013, Ku and Bae 2014. The antiplatelet activity occurs due to the presence of alkaloids which is already reported in different studies (Chen et al, 1996).…”
Section: Discussionmentioning
confidence: 86%